Answer:
[tex]9x^{4a} -24x^{2a}y^{a} z^{3a} + 16y^{2a} z^{6a}[/tex]
Step-by-step explanation:
You can follow this steps:
For the expression:
[tex](3x^{2a} - 4y^{2} z^{3a} )^{2}[/tex]
Write the factors:
[tex](3x^{2a} - 4y^{2} z^{3a} )(3x^{2a} - 4y^{2} z^{3a} )[/tex]
Now multiply by the term [tex]3x^{2a}[/tex]
[tex](3x^{2a} - 4y^{2} z^{3a} )(3x^{2a} - 4y^{2} z^{3a} ) = 9x^{4a} -12x^{2a} y^{a} z^{3a}[/tex]
Then multiply by the term [tex]-4y^{2}[/tex]
[tex](3x^{2a} - 4y^{2} z^{3a} )(3x^{2a} - 4y^{2} z^{3a} ) = 9x^{4a} -12x^{2a} y^{a} z^{3a} \\\\ -12x^{2a} y^{a} z^{3a} + 16y^{2a} z^{6a}[/tex]
Finally add the terms:
[tex]= 9x^{4a} -24x^{2a} y^{a} z^{3a} + 16y^{2a} z^{6a}[/tex]
You will need to review the laws for the exponents.
For example:
When you are multiplying with the same base you need to add the exponents.
[tex]x^{2} *x^{5} = x^{2+5} = x^{7}[/tex]
Power to power, you multiply the exponents but keep the same base:
[tex](x^{2}y)^3 = (x^{2*3} y^3) = x^{6} y^3[/tex]